Challenging Nominee Agreements in the Mining Industry: Between Constitutional Mandates and Legal Evasion - Sumarsih, Ida (Indonesia Law Review, 2025)
The restriction of foreign ownership in Indonesia’s mineral and coal mining sector is intended to uphold national sovereignty over natural resources and ensure equitable public welfare. However, these objectives are undermined by the widespread use of nominee agreements, a form of legal circumvention that enables foreign investors to covertly maintain control over mining operations. This normative juridical study, based on secondary legal sources and inductive analysis, finds that the persistence of nominee practices is primarily due to inadequate regulatory oversight and weak law enforcement. As a result, the benefits of mining activities are diverted away from the Indonesian people, contradicting the constitutional mandate that natural resources be utilized for the greatest possible prosperity of the population. The study recommends the establishment of a coordinated regulatory framework involving the Ministry of Energy and Mineral Resources, the Directorate General of Mineral and Coal, the Ministry of Law and Human Rights, and the Investment Coordinating Board to monitor beneficial ownership structures and enforce existing prohibitions on nominee arrangements. Strengthening these mechanisms is essential to safeguard Indonesia’s resource sovereignty and ensure the fair distribution of mining revenues.